2014
DOI: 10.4028/www.scientific.net/amr.1079-1080.354
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Double-Wall Precast Concrete Shear Wall under Low-Cyclic Reversed Loading Test

Abstract: This paper describes an ongoing research program on the seismic resistance performance of the double-wall precast concrete (DWPC) shear wall. Low-cyclic reversed loading test of three new full scale specimens are carried out based on the previous studies. The test results indicate that DWPC shear walls have higher initial stiffness, cracking load, yielding load and ultimate load. The displacement ductility ratios of DWPC shear walls are no less than that of cast-in-situ shear wall. The hysteretic curves of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…After being installed in place, concrete is poured in the middle of the two layers, bearing the vertical horizontal force together. Through the test [36][37][38][39][40], it can be seen that the prefabricated part of this superimposed wall is well combined with the cast-in-place part, and the energy dissipation capacity is similar to that of the whole cast-in-place wall, which proves that the seismic performance is close to the traditional cast-in-place wall.…”
Section: Introductionmentioning
confidence: 97%
“…After being installed in place, concrete is poured in the middle of the two layers, bearing the vertical horizontal force together. Through the test [36][37][38][39][40], it can be seen that the prefabricated part of this superimposed wall is well combined with the cast-in-place part, and the energy dissipation capacity is similar to that of the whole cast-in-place wall, which proves that the seismic performance is close to the traditional cast-in-place wall.…”
Section: Introductionmentioning
confidence: 97%
“…However, the labor cost has recently increased significantly in China, and energy conservation as well as environmental protection has attracted increasing attention. As a result, research on the precast concrete structures has become increasingly popular (Jiang et al, 2011;Lu et al, 2008;Qian et al, 2011;Sun et al, 2015;Xiao et al, 2015;Xue et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, research on the seismic performance of a superimposed RC wall structure is rarely reported, because this structure was mostly adopted to construct low-rise and mid-rise buildings in the non-seismic regions of some European countries (such as Germany and the United Kingdom). After this type of structure was introduced to the seismic regions of China, the authors of this article and a number of researchers have conducted some seismic experimental studies (Chong et al, 2010;Wang et al, 2012;Xiao et al, 2015); however, most of these were limited to single wall panels. Unlike single wall panels, in real RC wall structures, walls usually have transverse components attached as the flanges, forming Tshaped or I-shaped cross-section shear walls.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major issues that limit the acceptance of precast shear walls in construction industry is the laborious process of transportation and installation due to their heavy mass. The concern can be addressed by the development of hollow precast shear wall system, also known as composite walls or sandwich walls. Sandwich systems are also advantageous for tall precast walls, where the weight of precast panel exceeds the limit of load carrying capacity of cranes available.…”
Section: Discussionmentioning
confidence: 99%